Chaiyo! King Vajiravudh and the Development of Thai Nationalism - Vella, Walter F. (University of Hawai'i Press, 2018)
Throughout his fifteen-year reign (1910-1925), King Vajiravudh, absolute monarch of Siam, attempted to foster a spirit of nationalism among the Thai, to unite the Thai people and make them proud of their land and their heritage. He hoped to save his country from expanding Western imperialism by infusing his people with the Western ideology of loyalty to the state.This book documents all the many forms the King's nationalistic efforts assumed, ranging from the establishment of a para-military patriotic organization called the Wild Tiger Corps to the encouragement of the team sports and the coining of a new cheer, Chaiyo! ("Victory!"). Vajiravudh was a prolific writer, and his hortatory articles, plays, poems, and speeches are analyzed in terms of the King's message to his people to be Thai, to act Thai, and to think Thai.Chaiyo! adds greatly to an understanding of the emergence of modern Thailand. It is also an important addition to studies of the impact of the West and the emergence of nationalism in Asia as a whole during the period of World War I. The findings will be of value not only to historians but also to political scientists and, indeed, to all those interested in the development of Asia or in the growth of nationalism anywhere in the world.